Compassionate Care: A Qualitative Exploration of Nurses' Inner Resources in the Face of Burnout - Sarah-Louise d'Auvergne Flowers; Mireia Guillén-Solà; Noemí Sansó; Laura Galiana (MDPI AG, 2024)
There is a universal shortage of nurses, with a current needs-based shortage of 5.9 million. This is not solely a recruitment issue but one of retention, triggered by high levels of work-induced stress, burnout, and reports of low job satisfaction resulting in poor care delivery. Some of the health repercussions on nurses include anxiety, insomnia, depression, migraines, irritability, absenteeism, and sometimes alcoholism and drug abuse. To tackle some of these costly issues, a qualitative exploration into how inner resources is used by nurses to cope with stress at different points of their careers is proposed. Through the lens of grounded theory, semi-structured interviews will be carried out with two distinct sets of participants: (1) Student nurses registered at the University of the Illes Baleares between 2022-2025. (2) Experienced nurses on the Balearic nursing register. Interviews will be coded and then analysed using Atlas.ti. Expected results will inform curriculum improvements that will benefit the well-being of (student) nurses, from the outset of their training, pre-empting potential psycho-social risks before they arise in the workplace. This is vital as it addresses nurses' mental health as well as chronic issues of retention and absenteeism.